Heat transition in the European building sector: Overview of the heat decarbonisation practices through heat pump technology. (December 2021) - Abbasi, Mohammad Hosein; Abdullah, Badr; Ahmad, Muhammad Waseem; Rostami, Ali; Cullen, Jeff
Graphical abstract: Highlights: Key issues to roll out heat pumps are identified based on the evidence from practices. Heat pumps cannot serve as a stand-alone substitute for gas boilers. Hybrid heat pump is a low-regret transitionary solution towards full decarbonisation. A trend to small-scale and individual systems is noticeable in policies and practices. Upgrades in the building and electricity sectors are prerequisites for promotions. Abstract: Decarbonisation of heating and cooling in the built environment has been recognised as a necessity to achieve any energy and climate change targets. Heat pumps (HP) are one of the technologies that are extremely validated and utilised in the European heat decarbonisation pathways. However, many challenges and uncertainties still lie ahead of HPs in research, practices and policymaking. Practical evidence from real-world case studies could mitigate some of these uncertainties and accelerate the rollout of HPs. Hence, this research aims to present an overview of the key issues and challenges which emerge from the heat decarbonisation practices through HP technologies across the EU. Adopting the evidence-based approach, experiences from the best practices are synthesised, as well as addressing the state-of-the-art and trends of HPs in the EU. Finally, the key factors and insights which are needed to be considered over the design, implementation and operation of HPs are identified and discussed. The conclusions highlight the significant potential of HPs in consolidated solutions such as hybrid HPs, local heat synergies and heat networks. Heat pumps combined with complementary technologies are ready to serve the first wave of heat transition across Europe. However, regulatory provisions, building upgrades and development of other complementary components must be accelerated to keep pace with the HP initiatives.